Promotion and protection of cultural heritage through interdisciplinary approaches: The case of Souli - Konstantinidou , Elena; Pantazis , George (Technical Annals, 2022)
"Μapping" a place, through systematic recording, analysis, evaluation and interpretation of its characteristics, is a necessary condition and basic tool for its protection and promotion. "Reading" a place through different scientific areas, includes perspectives and interpretations that converge and interact. These approaches highlight multiple issues for a place, contributing to its "recognition" through time as well as its promotion. The paper focuses on the contribution and importance of the interdisciplinary approaches and cooperation in cultural heritage management issues, on the occasion of a research carried out for Souli, one of Greece’s most important historical sites. Emphasis is given on the issues of Geometric survey and documentation and the relation to the overall levels of recognition and interpretation of space, through the example of the historic site of Souli. The correlation of geometric to interpretive approaches, quantitative and "metric" recordings to qualitative and intangible characteristics, also the production of a "tool" that contains as much as quantitative as quality features, are basic concerns of this paper.